1991
DOI: 10.1111/j.1365-2648.1991.tb01593.x
|View full text |Cite
|
Sign up to set email alerts
|

The concept of hope revisited for nursing

Abstract: The development of nursing knowledge and interventions involve understanding human responses and needs. The human response of hope was identified as a concept in need of further clarification. The purpose of this paper was to review definitions and contextual usage of the word 'hope' from the literature and answer the conceptual question 'What is hope?' Literature from theology, philosophy, psychology and nursing was reviewed for contextual usage of the word 'hope'. In the literature, hope was viewed as part o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
104
0
3

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(107 citation statements)
references
References 22 publications
0
104
0
3
Order By: Relevance
“…Hope protects against the stress generated by disease and enables individuals to reassess their situation, seek strategies, and get involved in health behaviors, which contribute to treating the disease and, in turn, contributes in the adaptation. (28) The results suggests, that hope is a prerequisite for coping (7) and both variables influence upon the perception of social support as interdependence mode. However, the effect of hope and social support on active aging was lost, only coping with aging persists.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…Hope protects against the stress generated by disease and enables individuals to reassess their situation, seek strategies, and get involved in health behaviors, which contribute to treating the disease and, in turn, contributes in the adaptation. (28) The results suggests, that hope is a prerequisite for coping (7) and both variables influence upon the perception of social support as interdependence mode. However, the effect of hope and social support on active aging was lost, only coping with aging persists.…”
Section: Resultsmentioning
confidence: 91%
“…Contextual stimuli are those that although present in a given situation, do not demand energy and immediate attention from the individual, but do contribute to the effect of the focal stimulus and influence upon the situation. (6) This study proposed hope and sociodemographic variables as contextual stimuli; given that the literature indicates that hope is a precursor of effective coping and decision making, (7) as in this case in treating the disease and of active aging.…”
Section: Introductionmentioning
confidence: 99%
“…It is increasing suggested that nurses are an important source of hope for people who are vulnerable and ill (Herth 1990, Stephenson 1991, Herth 1996, Cutcliffe & Grant 2001, Moore 2005; due to their constant interaction with patients who are suffering.…”
Section: The Contribution Of Nursing and The Relevance Of Hope To CLImentioning
confidence: 99%
“…Hope is defined in research as considering possibilities of future positive outcomes (Stephenson, 1991), the likelihood of improving upon cunent or past situations, or considering "perceived capacity to use one's pathways to reach desired goals" (te Riele, p. 36). Within these definitions, hope may be considered futureoriented, and throughout this project, the hoped-for future of participants and their families influenced family communication about sexuality.…”
Section: Hopementioning
confidence: 99%